Dipyrrolyldiketone PtII Complexes: Ion‐Pairing π‐Electronic Systems with Various Anion‐Binding Modes. Issue 39 (4th June 2021) - Kuno, Atsuko; Hirata, Goki; Tanaka, Hiroki; Kobayashi, Yoichi; Yasuda, Nobuhiro; Maeda, Hiromitsu
Abstract: A variety of π‐electronic ion‐pairing assemblies can be constructed by combining anion complexes of π‐electronic systems and countercations. In this study, a series of anion‐responsive π‐electronic molecules, dipyrrolyldiketone Pt II complexes containing a phenylpyridine ligand, were synthesized. The resulting Pt II complexes exhibited phosphorescence emission, with higher emission quantum yields (0.30–0.42) and microsecond‐order lifetimes, and solution‐state anion binding, as revealed by our spectroscopic analyses. These Pt II complexes displayed solid‐state ion‐pairing assemblies, exhibiting various anion‐binding modes, which derived from pyrrole‐inverted and pyrrole‐non‐inverted conformations, and packing structures, with the contribution of charge‐by‐charge assemblies, which were dependent on the substituents in the Pt II complexes and the geometries and electronic states of their countercations. Abstract : Dipyrrolyldiketone Pt II complexes, as phosphorescence‐emitting and anion‐responsive π‐electronic systems with planar geometries, were synthesized to construct ion‐pairing assemblies in the form of anion complexes. The ordered arrangements of the anion complexes and countercations, including porphyrin Au III complexes, were formed via noncovalent interactions between oppositely and identically charged species in the solid state.